Identifying Extension Information Delivery Methods For Environmental Issues - Timothy J. Rollins; Thomas B. Bruening; Rama B. Radhakrishna (Journal of Applied Communications, 1991)
The primary purpose of this study was to identify the types of information sources that farmers find useful, and the human resource organizations they depend upon when confronted with environmental issues.